Pengujian Perangkat Lunak Menggunakan Metode Regression Testing pada Aplikasi Pembelajaran Matematika untuk Siswa Tingkat Smp Berbasis Android - Syita Luginawati; Ari Purno Wahyu (Syntax Idea)
Technological developments have caused several significant changes in the world of education. One of them is as a learning media. Currently, students at every level of education are familiar with the use of devices as learning media. Through technology, it is easier for them to access every material so that it is easier to learn it. As a result, learning media applications that can be used in students' mobile devices to facilitate their activities are increasingly being loved lately. However, applications with various features and advantages will certainly leave gaps in application vulnerabilities and other errors. Therefore, this study aims to determine the readiness of the application when used in bulk and minimize errors that occur to maintain the integrity of the application so that it can be used properly by users using the Regression Testing method. In this study the application used was the Mathematics Learning Application for Android-Based Middle School Level Students.